Just and unjust military intervention European thinkers from Vitoria to Mill - Recchia, Stefano; Welsh, Jennifer M. (Cambridge University Press, 2013)
Classical arguments about the legitimate use of force have profoundly shaped the norms and institutions of contemporary international society. But what specific lessons can we learn from the classical European philosophers and jurists when thinking about humanitarian intervention, preventive self-defense or international trusteeship today? The contributors to this volume take seriously the admonition of contextualist scholars not to uproot classical thinkers' arguments from their social, political and intellectual environment. Nevertheless, this collection demonstrates that contemporary students, scholars and policymakers can still learn a great deal from the questions raised by classical European thinkers, the problems they highlighted, and even the problematic character of some of the solutions they offered. The aim of this volume is to open up current assumptions about military intervention, and to explore the possibility of reconceptualizing and reappraising contemporary approaches.